Cystic fibrosis - Ways to improve the quality of life of patients - Świercz, Kamila; Majcher, Magdalena; Górska, Dominika; Majcher, Monika; Karwańska, Aleksandra; Pikulicka, Agata; Sierpień, Małgorzata; Brzychczy, Piotr; Kulbat, Aleksandra; Kulbat, Mateusz (Journal of Education, Health and Sport, 2023)
Introduction Cystic fibrosis (CF) is a serious, multi-system disease. In the Caucasian population CF is the most common autosomal recessive disease, which happens for 1 person in 3,500 births [1]. In the course of CF, there is a dysfunction of many organs, mainly the respiratory and digestive systems. Symptomatic treatment of cystic fibrosis is very important. The change in daily eating habits, the use of proper breathing techniques and psychotherapy also have an impact on improving the quality of life of patients. In the past patients died at a young age. The progress in the diagnosis and treatment of cystic fibrosis has meant that nowadays more and more people are reaching adulthood. In recent years, the median survival of patients has increased to 46.2 years. [2] Purpose The aim of this review is to present the current state of knowledge about ways to improve the quality and length of life of patients with CF. Methods The literature available in the Pubmed and Google Scholarship databases was reviewed using key phrases. Results Additional methods of treatment, such as: learning the correct breathing technique, oxygen therapy, physical exercise or proper nutrition, significantly improve the living conditions of patients.